Emerging Trends in Bilosomes as Therapeutic Drug Delivery Systems - Hemlata Kaurav; Meenakshi Tripathi; Simran Deep Kaur; Amit Bansal; Deepak N. Kapoor; Sandeep Sheth (MDPI AG, 2024)
In recent years, there has been a notable surge in the utilization of stabilized bile acid liposomes, chemical conjugates, complexes, mixed micelles, and other drug delivery systems derived from bile acids, often referred to as bilosomes. The molecular structure and interactions of these amphiphilic compounds provide a distinctive and captivating subject for investigation. The enhanced stability of new generation bilosomes inside the gastrointestinal system results in the prevention of drug degradation and an improvement in mucosal penetration. These characteristics render bilosomes to be a prospective nanocarrier for pharmaceutical administration, prompting researchers to investigate their potential in other domains. This review paper discusses bilosomes that have emerged as a viable modality in the realm of drug delivery and have significant promise for use across several domains. Moreover, this underscores the need for additional investigation and advancement in order to comprehensively comprehend the prospective uses of bilosomes and their effectiveness in the field of pharmaceutical administration. This review study explores the current scholarly attention on bilosomes as prospective carriers for drug delivery. Therapeutic areas where bilosomes have shown outstanding performance in terms of drug delivery are outlined in the graphical abstract.